«Clara Peeters and their other Stories»: teaching innovation proposal to deal with resistance and prejudices in training teacher of the master in secondary teacher training - Triviño Cabrera, Laura (Revista Complutense de Educación, 2017)
This article tries to explain the results obtained in a teaching innovation project which joins education and cultural heritage. Taking advantage of the holding the exhibition “The Art of Clara Peeters” (autumn, 2016), the first exhibition devoted to a woman painter in the Prado Museum, we developped a interdisciplinary project-based learning with students from Master in Secondary Teacher Training, specialize in Social Sciences, of the Málaga University. They had to organize several activities for students from secondary education who had the opportunity of knowing the role of the women in the history and the art, other stories, other geographies, still life paintings o the daily life. In this Project, there were applied these methodologies: service-learning, problem based learning, collaborative learning, cooperative learning and flipped classroom. This projet would achieve the following goals: the elimination of prejudices concerning the perception of the master as a necessary formality, the enlargement of the practical dimension, the implementation of innovative methodologies, the interdisciplinary approach, the teamwork and the knowledge the existence of a “hidden curriculum”.